Kesulitan Belajar Siswa pada Pembelajaran Matematika Materi Operasi Hitung Pecahan Kelas V SDN 02 Pakisrejo - Rohmah, Silvia Lailatur; Jadmiko, Rahmad Setyo (Universitas Nusantara PGRI Kediri, 2024)
Learning difficulties are a condition where students cannot learn and receive the learning material properly as they should. The purpose of this study was to determine the learning difficulties of fifth grade students in learning mathematics on fractional arithmetic operations at SDN 02 Pakisrejo. The research method used is qualitative research with a case study approach. The instruments used in this study were test sheets and observations. The results of this study are the learning difficulties of mathematics on fractional arithmetic operations for fifth grade students of SDN 2 Pakisrejo Tulungagung are; 1) As many as 7 out of 13 students or 54% of students have difficulty learning in using concepts, 2) As many as 7 out of 13 students or 54% of students have difficulty using principles, and 3) As many as 6 out of 13 students or 46% of students have difficulty using verbal problems.